FACTORS AFFECI1NG ENVIRONMENTAL SANITATION AND "ROLES OF SANITARY OFFICERS IN THE 21ST CENTURY IN ESAN WEST" LOCAL GOVERNMENT AREA OF EDO STATE. - RICHARD ONOIGBORIA OKAKA, RICHARD ONOIGBORIA OKAKA; OKONIGENE D., OKONIGENE D. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
The paper tried to examine the factors affecting environmental sanitated and the roles of sanitary officers in the 21st century in Esan West Local Government Area of Edo State. The paper tried to define environmental sanitation, the role of good environmental sanitation, the economic benefits and the good junctions of environmental health officers. The paper concluded that environmental sanitation is the basis for the protection, promotion and reservation of good health and therefore recommended amongst others that the government must create budget for environmental health programs, and that private sector participation should be encouraged.